A snapshot of data quality issues in Indonesian community health. (1st January 2014) - Aisyah, Maulidyati; Cockcroft, Sophie
Healthcare services in Indonesia remain 'poor' by international standards. At the heart of the problem are systemic data quality issues. Little work has been done on health data quality in rural settings in this region. In this work, an exploratory study of data quality within a health centre (HC) in rural Indonesia is carried out with reference to two well-known sets of qualitative data quality measures AIMQ and PRISM. The research aims first to uncover data quality issues within a typical health facility in rural Indonesia, and second to discover whether these problems relate to operational issues. The research uses an inductive, qualitative case study approach using the following methodology. Key data quality issues are identified in the literature; these are used as a framework from which to develop seed questions for data collection via semi structured interviews. The full interview transcripts are analysed manually and using the text mining software Leximancer. Issues relating to data validation and integration are identified. Suggestions are put forward for development action both locally and nationally. This work provides a snapshot of the state of play in a typical rural health facility in Indonesia.